Genomic and Phenotypic Insights Into the Potential of Rock Phosphate Solubilizing Bacteria to Promote Millet Growth in vivo - Silva, Ubiana C.; Cuadros-Orellana, Sara; Silva, Daliane R. C.; Freitas-Júnior, Luiz F.; Fernandes, Ana C.; Leite, Laura R.; Oliveira, Christiane A.; Dos Santos, Vera L. (Frontiers in Microbiology, 2021)
Rock phosphate (RP) is regarded as a natural source of phosphorus for agriculture, with the advantage of lower cost and less impact on the environment. However, the release of P from RP occurs slowly, which may limit its availability to crops short-term. Hence, the use of P-solubilizing microorganisms to improve the availability of P from this P source has been proposed. This is an interesting approach, as microorganisms often perform other functions that assist plant growth, besides solubilizing P. Here, we describe the isolation of bacteria from the rhizosphere of maize plants cultivated in soil treated with RP and in soil that did not receive any fertilization. Using this culture-based approach, bacteria belonging to the family Enterobacteriaceae, mainly Klebsiella and Enterobacter, were predominantly obtained. These bacteria, together with endophytic bacteria previously isolated from maize plants, were characterized based on their P solubilizing activity in vitro, their growth-promoting activity on millet plants cultivated in soil amended with RP, and their gene content especially associated with phosphate solubilization. For the in vitro solubilization assays, two mineral P sources were used: rock phosphate from Araxá (Brazil) mine (AP) and iron phosphate (Fe-P). The amounts of P released from Fe-P in the solubilization assays were lower than those released from AP, and the endophytic bacteria outperformed the rhizospheric ones in the solubilization of both P sources. Six selected bacteria were evaluated for their ability to promote the growth of millet in soil fertilized with AP, and all except one (Microbacterium sp. UFMG61) contributed to the improvement of at least one of the growth parameters of this plant. Also, considering RP solubilization , all bacteria improved at least one parameter of the P soil concentration or its content in the plant. Among these, Bacillus megaterium UFMG50 and Ochrobactrum pseudogrignonense CNPMS2088 performed best in the AP assays. Genomic analysis of these bacteria revealed the presence of genes related to P uptake, organic acid and phytohormone synthesis. Using this approach, we identified potential candidates for soil inoculants aimed at improving rock phosphate solubilization and plant growth, which are promising for use under field conditions.